Analysis of Economic Adjustments as a Result of a Deep Crisis: the Case of Latvia - Lešinskis, Kristaps (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2010)
The Latvian economy has been the most crisis affected economy so far in the whole territory of the EU. The expected GDP fall during the year 2009 is close to 20%, the unemployment rate is approaching 20%, and prices have already started to fall. There are major fiscal problems in the economy. For the second year Latvian society has lived under the threat of devaluation of the national currency. The country has applied for serious external financial assistance from the IMF and the European Commission. The sharp decrease in the economic activity is strongly related to the high current account deficit in the balance of payments which developed during the previous years of a high growth thus making the Latvian economy extremely vulnerable. As a financial inflow has strongly decreased, there is a rapid decline in both private and government consumption and investment. This paper is aimed at analysing and explaining the roots of the drastic changes in almost all macroeconomic indicators that have led to serious economic adjustments and strict changes in the economic policy. The paper will assess the outcomes of the economic adjustments as well as extract the most important lessons that have to be taken from what has happened in the crisis most affected economy of the EU. Both a quantitative analysis of indicators and a qualitative analysis of economic policy decisions are analysed within this paper.